First record of Anselmella malacia Xiao & Huang, 2006 (Hymenoptera: Eulophidae), a new insect pest of water apple (Syzygium samarangense) and its associated parasitoid in Dong Thap Province, Vietnam - Oanh, Nguyen Thi; Bup, Nguyen Kim; Long, Khuat Dang (Academia Journal of Biology, 2019)
The eulophid wasp, Anselmella malacia Xiao & Huang, 2006 (Hymenoptera: Eulophidae), is reared from fruits of the water apple, Syzygium samarangense, and is reported as an important phytophagous developing as seed-eaters of Syzygium species in Malaysia. Analysing specimens of pest insects infested inside of pear-shaped fruits of the cultivated water apple, S. samarangense, in Dong Thap Province, South Vietnam, a total of four insect species were recorded as the important pests for fruits of six varieties of the cultivated water apples. The hymenoteran wasp, A. malacia, is recorded for the first time from Vietnam. Further evidence is needed to prove A. malacia being an invasive pest in Vietnam. The associated hymenopteran parasitoid assemblage with the fruit infested insect pests is also provided.